Analysis of the evolution of Romania's foreign trade in natural honey - Aurelian Buliga-Ṣtefănescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Romanian honey, a food product of higher quality compared to that obtained in other European countries, is exported extensively (50-60% of the total production). Currently, the Romanian beekeepers are facing the tough competition of the low prices of the honey imported from Ukraine, Poland and the Republic of Moldova. Germany is the largest importer of honey (26%) from Romania. In 2018, Romania exported honey amounting to a total of 41.7 million euros .The Romanian market still sells products at low prices, to the detriment of quality, which is why, in the same year, about 9.7 million euros'worth of honey was imported. In the whole period analyzed (1991-2018) the value of honey exports was significantly higher than the value of imports, thus generating a positive balance of trade.
Keywords: Q10; Q13; Q17; O13; 330; honey production; honey import; honey export